A comparison of optimal tax policies when compensation or responsibility matter - Laurence Jacquet; Dirk van de Gaer (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper examines optimal redistribution in a model with high- and low-skilled individuals with heterogeneous tastes for labor. We compare the extent to which optimal policies based on different normative criteria obey the principles of compensation (for differential skills) and responsibility (for preferences for labor) when labor supply is along the extensive margin. With heterogeneity in skills and preferences, traditional Welfarist criteria including Utilitarianism present unappealing policy recommendations in some scenarios as they fail to take compensation and responsibility issues into account. Criteria from the social choice literature perform better in this regard in first-and second-best. More importantly, these equality of opportunity criteria push the second-best policy away from an Earned Income Tax Credit and in the direction of a Negative Income Tax.
Keywords: H21; D63; 330; optimal income taxation; equality of opportunity; heterogeneous preferences for labor; Optimale Besteuerung; Einkommensteuer; Soziale Wohlfahrtsfunktion; Verteilungsgerechtigkeit; Asymmetrische Information; Theorie